Severity of emphysema as a prognosticator of resected early lung cancer: an analysis classified by Goddard score. (10th June 2020) - Kagimoto, Atsushi; Mimura, Takeshi; Miyamoto, Tatsuya; Nakashima, Chika; Yamashita, Yoshinori
Abstract: Objectives: This study aimed to investigate whether the severity of emphysema as classified by Goddard score influences the prognosis of patients with early lung cancer, there are few reports about that. Methods: From April 2009 to December 2016, we recruited 412 consecutive patients with completely resected clinical stage 0/IA/IB non-small cell lung cancer. The Goddard score assessed on preoperative computed tomography scan was retrospectively reviewed. Kaplan–Meier and Cox regression analyses were performed to assess the relationship between the Goddard score and early lung cancer prognosis. Results: The patients were classified into two groups: Goddard score ≤ 4 points and ≥5 points according to the results of receiver operating characteristic curve analysis for recurrence events. The 3-year relapse-free survival rate of emphysema with Goddard score ≤ 4 points (88.6%) was higher than that of emphysema with Goddard score ≥ 5 points (60.8%) ( P < 0.001). There was a higher proportion of cancer-related deaths in the group with Goddard score ≥ 5 points compared with the group with Goddard score ≤ 4 points (50% and 32.1%, respectively) ( P = 0.082). A Goddard score ≥ 5 points was a significant prognostic factor for relapse-free survival in the univariate ( P < 0.001) and multivariate ( P = 0.022) analyses. A Goddard score ≥ 5 points was also a significant prognostic factor for overall survival in the univariate ( P < 0.001) and multivariate ( P = 0.041) analyses. Conclusion: Our findings suggest that emphysema with a Goddard score of ≥5 points may be a factor that can influence the prognosis of patients with primary lung cancer. Abstract : Pulmonary emphysema with a GS of ≥5 points may be a factor that can influence the prognosis of patients with primary lung cancer.